1994
DOI: 10.1111/j.1540-5915.1994.tb00516.x
|View full text |Cite
|
Sign up to set email alerts
|

User Perceptions of Decision Support Effectiveness: Two Production Planning Experiments*

Abstract: Decision support systems continue to be very popular in business, despite mixed research evidence as to their effectiveness. We hypothesize that what-if analysis, a prominent feature of most decision support systems, creates an "illusion of control" causing users to overestimate its effectiveness. Two experiments involving a production planning task are reported which examine decision makers' perceptions of the effectiveness of what-if analysis relative to the alternatives of unaided decision making, and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…The two complex tasks consisted of a facility location task (the complex-symbolic task) (Buffa, 1990) and an aggregate planning task (the complex-spatial task) (Holt et al, 1960;Remus, 1984Remus, , 1987Davis and Kotterman, 1994). In the facility location task, subjects were provided with five different cost estimates associated with six warehouse locations.…”
Section: Article In Pressmentioning
confidence: 99%
“…The two complex tasks consisted of a facility location task (the complex-symbolic task) (Buffa, 1990) and an aggregate planning task (the complex-spatial task) (Holt et al, 1960;Remus, 1984Remus, , 1987Davis and Kotterman, 1994). In the facility location task, subjects were provided with five different cost estimates associated with six warehouse locations.…”
Section: Article In Pressmentioning
confidence: 99%
“…In experiments where gamblers have been presented with pseudo-controlling situations (e.g., picking their own number in a lottery; Burger, 1991) or bogus artefacts misconstrued as control-enhancers (e.g., using a reel-stopping device in a video lottery terminal game; Ladouceur & Sévigny, 2005), it has been demonstrated that gamblers consistently prefer these options when presented even if these actions have no instrumental impact on gambling outcomes. In other contexts, researchers have also found that people tend to exaggerate the benefits of devices that enhance the illusion of control, and fail to detect that such devices do not offer any advantage in gambling outcomes (Davis & Kottemann, 1994).…”
Section: Control Perception In Gamblingmentioning
confidence: 99%
“…The ANOVA of the attitude scale by the experimental variable was not significant. The borderline significance may be explained by Davis and Kottemann's (1994) suggestion that DSS users' attitudes may not relate to its actual effectiveness.…”
Section: Optimism's Influence On Emotionsmentioning
confidence: 74%